PENGARUH MODEL PROBLEM-BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI TEKANAN ZAT - Juliper Nainggolan; Asnida; Januaris Pane; Lestari Silalahi (Pendidikan Fisika UIN Alauddin Makassar, 2022)
This study aims to determine the effect of the problem-based learning model on student learning outcomes in the material pressure of class VIII SMP Negeri 2 Manduamas. This type of research is quasi-experimental, the research sample consists of two classes, namely VIII-C as the experimental class and VIII-B as the control class, each consisting of 30 students. The research instrument is a learning activity observation sheet and multiple-choice objective tests to determine student learning outcomes. Based on the calculation of the t-test of the two parties, the pretest data = 0.05, it was obtained that H0 was accepted, that the initial abilities of the experimental class and control class students were the same. After being given different treatment, the results of the one-sided t-test calculation for posttest data for =0.05 were obtained tcount = 3.80 and ttable = 1.67 with tcount > ttable, then Ha was accepted. The relationship of each variable has a significant effect with the regression equation = 1.27 + 1.00X. So it was concluded that there was a significant effect of the problem-based learning model on the learning outcomes of eighth grade students of SMP Negeri 2 Manduamas.